Environmental Technology in the Oil Industry - Orszulik, Stefan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This significantly updated edition looks at each stage in the life cycle of petroleum products, from exploration to end use, examining the environmental pressures on the oil industry and its response. Technical developments are progressing in line with environmental concerns and increasing sophistication of computer modelling techniques. These subjects are interrelated, but have often been dealt with independently. This book explores these topics together in a way that is understandable to the non-expert, and those who are expert in one field, but wish to see their expertise discussed in the overall context. Written primarily for those working in the oil and related industries, this book also provides essential reference material for government and research institutions and all those with an interest in environmental technological issues.
General Introduction -- Environmental Control Technology for Oilfield Processes -- Environmental Control of Well Integrity -- Environmental Control of Drilling Fluids and Produced Water -- Oilfield Waste Disposal Control -- Environmental Imacts of Hydraulic Fracturing -- Drilling and Production Discharges in the Marine Environment -- Decommissioning of Offshore Oil and Gas Installations -- Tanker Design and Safety: Historical Developments and Future Trends -- Environmental Management and Technology in Oil Refineries -- The Marketing, Distribution and Use of Petroleum Fuels -- Lubricants -- Climate Change Scenarios and their Potential Impact on World Agriculture.
Keywords: Chemistry, Technical; Environmental chemistry; Industrial engineering; Production engineering; Cogeneration of electric power and heat; Fossil fuels; Industrial Chemistry; Environmental Chemistry; Industrial and Production Engineering; Fossil Fuel